Prospects for the Development of Eco-Tourism in Surkhandarya Region (Eurasian Journal of History, Geography and Economics, 2023)
This article talks about the prospects for the development of ecological tourism in the Surkhandarya region. Based on archival data, the author analyzed the problem on the basis of existing scientific literature and studied the existing specific aspects of the development prospects of ecological tourism in Surkhandarya region.